MODEL IMPLEMENTASI P5 MELALUI KARYA SENI TARI DENGAN JUDUL “TARI GEMARIPAH AREK SUROBOYO” SEBAGAI MEDIA MENUMBUHKAN MINAT BAKAT DI SDN DUPAK 1 SURABAYA - Nugroho, Kukuh Budi; Kaliwanovia, Tasiawati Salsa (Universitas Negeri Medan, 2024)
Abstract: The era of massive globalization is increasingly having an impact on learning loss or loss of learning due to lagging behind which is the impact of the Covid-19 pandemic. Responding to these problems, the Ministry of Education, Culture, Research and Technology launched the Independent Curriculum with an emphasis on learning on a project basis to support the creation of the Pancasila Student Profile character. This research aims to find out how to implement P5 through a dance work entitled